Cities rethinking innovation by technology - Mauro ROMANELLI (Smart Cities and Regional Development Journal)
As social organisms cities continuously change to ensure high quality of life for citizens and to provide services to business driving social, cultural and economic development and growth within urban ecosystems. Rethinking cities as communities looking at the future implies to jointly consider sustainability, innovation and information technology as sources and issues of city design. The future and sustainability of cities relies on developing sources for technology-enabled innovation that helps cities to be attractive communities that acquire intellectual capital and foster knowledge-based processes. Sustainable cities tend to develop knowledge creation and innovation over time in order to improve and extend the wealth of people within community.As smart communities, cities should identify a path for sustainability adopting a smart approach to urban development. The aim of the study is to elucidate how cities consider innovation driven by information technology as a source that helpsproceed towards sustainability. Cities promote and develop innovationin services, city design and city governance using information technology. The study is theoretical and relies on the analysis of literature that concerns the relationship between innovation and cities. Cities should select a path for sustainability promoting a smart approach in order to develop innovation by using information technology.The main contribution of this study is to elucidate how cities identify a path for sustainability investing organizational and strategic sources to develop innovation as a framework that drives processes of change and helps sustainability within urban ecosystems. Cities become communities oriented to promote sustainability developing smartness as a strategic orientation and approach for change, designing and implementing technology-enabled and citizen-centred services, constructing forms of governance that rely on engagement and participation of all urban stakeholders. As communities looking at the future, cities believe ad invest in innovation as a source that ensures social and economic growth as a means for value creation in urban ecosystems.